Pediatric portal hypertensive enteropathy after Kasai surgery - Ho Jong Jeon; Kyong Ihn; In Geol Ho; Seok Joo Han (Elsevier, 2024)
Background: Portal hypertensive enteropathy (PHE) can cause chronic or acute gastrointestinal (GI) bleeding. Although there is a consensus on the diagnosis and treatment guidelines for PHE in adults, there are few reports on children. We aimed to report the clinical progress and outcomes of children with PHE treated with Kasai surgery and compare them with those of adults with PHE. Methods: In total, 309 patients who underwent postoperative endoscopy were enrolled among 336 patients who underwent Kasai surgery for biliary atresia at Severance Children's Hospital between May 2005 and March 2022. Results: The PHE diagnosis rate was 15.2 % (n = 47). PHE was not diagnosed until 2012; however, the diagnosis rates significantly increased over time (13.3 % and 36.1 % between 2013 and 2017 and 2018-2022, respectively). Of the 47 patients diagnosed with PHE, 14 (29.8 %) had GI bleeding caused solely by PHE. None of the PHE patients required ICU care at the time of bleeding, compared to 32 (24.1 %) in the gastroesophageal varix (GEV) group. After initial management, the rates of re-bleeding, refractory bleeding, and mortality were 78.6 %, 28.6 %, and 0.0 %, respectively, in the PHE group. Conclusions: Pediatric PHE diagnosis rates after Kasai surgery have increased since clinicians have become aware of the existence of the disease. Pediatric PHE has a high re-bleeding rate (78.6 %), although fatal GI bleeding is rare compared to GEV. Diagnosis and treatment of pediatric PHE can be performed according to adult guidelines. Level of evidence: III.